2012
DOI: 10.1177/0022034512455800
|View full text |Cite
|
Sign up to set email alerts
|

Degradation in the Fatigue Resistance of Dentin by Bur and Abrasive Air-jet Preparations

Abstract: A supplemental appendix to this article is published electronically only at http://jdr.sagepub.com/supplemental.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…Tooth fracture is more likely to originate from cracks that initiate and grow within the dentin. Flaws in the form of cracks can be introduced within the dentin during the restorative process as a result of material removal [25,26]. As an alternative, cracks may develop in dentin from incipient flaws as a result of fatigue, particularly in regions of stress concentration posed by the restoration geometry [21].…”
Section: Fracture Properties Of Dentinmentioning
confidence: 99%
See 3 more Smart Citations
“…Tooth fracture is more likely to originate from cracks that initiate and grow within the dentin. Flaws in the form of cracks can be introduced within the dentin during the restorative process as a result of material removal [25,26]. As an alternative, cracks may develop in dentin from incipient flaws as a result of fatigue, particularly in regions of stress concentration posed by the restoration geometry [21].…”
Section: Fracture Properties Of Dentinmentioning
confidence: 99%
“…More recent work has shown that the processes used for cutting of dentin during the introduction of restorations can cause a substantial reduction in fatigue strength. Specifically, Majd et al [26] discovered that cutting of coronal dentin with either carbide cutting burs or an abrasive air jet (both clinically relevant) substantially degraded the stress-life fatigue resistance. Cutting with carbide burs reduced the apparent endurance limit by nearly 40% (Fig.…”
Section: Fatigue Properties Of Dentinmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Sehy and Drummond [15] could not identify visible or microscopic cracking in dentin after performing bur treatments. Majd et al [16] evaluated the influence of bur cutting and an abrasive air jet treatment on the fatigue strength of coronal dentin. Despite an increase in surface roughness with respect to control surfaces and development of a smear layer, flaws or cracks were not evident in the prepared surfaces and there was no change to the static strength.…”
Section: Damage and Flawsmentioning
confidence: 99%